Clinical and pathological examination of mycotoxicosis as an associated risk factor for colic in equine - Gomaa, N.; Rivas Caceres, Raymundo Rene; Elemiri, M.; Hegazy, Y.; Nassif, M.; Alcalá Canto, Y.; Barbosa Pliego, A. (2021)
A retrospective cohort study was conducted on two Egyptian horse farms with most of horses were suffered from abdominal pain to describe the associations between the occurrence of mycotoxicosis and equine colic. The farms owner complain was an unexpected increase in number of colic cases and deaths among horses. The association between colic and risk factors (sex, type of food either dry or mixed with roughages and hematobiochemical parameters) was compared using independent sample T-test. The associations between possible prognostic in dicators for colic caused by mycotoxicosis was estimated using logistic regression analysis model. The cumulative incidence, incidence rates for colic attacks, survival rate among diseased horses were additionally estimated. Our results showed that a total of 24 out of the 132 horses suffered from colic due to feeding of ration contaminated with high percent of mycotoxin including Aflatoxins, Ochratoxins and or fusarium mycotoxins. The total cu mulative incidence of colic due to mycotoxicosis was 19.7%. The horses fed on dry rations had more chance of developing colic than horses fed on mixed rations (P < 0.05). The overall incidence rate of colic due to myco toxicosis was estimated at 18 colic attack/1000 horse/month. The mortality rate of horses suffered from colic due to mycotoxicosis was estimated at 5.9% (5/85), while the case fatality rate was estimated at 25% (n = 5/20). Inconclusion, our results showed that mycotoxicosis are considered an important risks factor for colic cases development in equine practice.